Dual marker one day pancreolauryl test. Issue 5 (May 1993) - Green, M R; Austin, S; Weaver, L T
Abstract : There is a pressing need for a simple non-invasive test of exocrine pancreatic function for use in children. The pancreolauryl test has been modified by the addition of a second marker (mannitol) to achieve a single day test without the need for two timed urine collections. Six healthy subjects and nine patients with cystic fibrosis were studied. Fluorescein, fluorescein dilaurate, and mannitol were taken by mouth, alone or in combinations, followed by 10 hour urine collections in two hourly aliquots to study the comparative pharmacokinetics of these markers. Urinary fluorescein was determined spectrophotometrically and urinary mannitol enzymatically. When fluorescein dilaurate and mannitol were taken together and the results expressed as ratios of percentage fluorescein to percentage mannitol recovery (F:M ratio) (mean (SD)) there was clear discrimination between healthy subjects and those with cystic fibrosis regardless of enzyme replacement treatment (57.3 (18.2) v 3.4 (1.4) v 3.2 (1.6) respectively). The differences in F:M ratios reached statistical significance in urinary aliquots collected between two and eight hours after marker ingestion. This single day tubeless test will greatly simplify the investigation of the child with suspected exocrine pancreatic dysfunction.